Challenges for rethinking a critical concept of law in the 21st century - Wolkmer, Antonio Carlos (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2025)
This article proposes as its main objective a reflection on the conditions of possibility of a critical conception of Law in the 21st century, recognizing the complexity and multiple interpretations that this proposition involves. Critical theory, traditionally seen as an instrument of resistance, rupture, resistance and emancipation, faces new challenges in the 21st century when applied to the institutional context of formal law, which has proven insufficient to address contemporary problems such as social inequalities, environmental crises, new forms of violence, racial discrimination, migration and neocolonialism. The central proposal of the article is to redefine critical thinking in Law, prioritizing the social, techno-communicational and ecological dimensions. The conclusion points to the need for an eco-social and counter-hegemonic civilizing project, inspired by the peripheral insurgencies of the South, which defends the urgency of life and the operationalization of a Human Right for the future.